Ham Helsing: Raising the Stakes - Book 3 3, Raising the stakes - Moyer, Rich; Lewis, Josh (Illustrator at Templar Books) (New York : RH Graphic, 2023)
While being snowed in at the old Helsing manor, Ham has his hands full trying to keep his friends safe from his very much alive legendary monster hunter dad.
Keywords: Swine -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Pigs -- Fiction; Monsters -- Fiction; Funny animal comics; Monster comics; Graphic novels